Porównanie portfeli Markowitza i portfeli o minimalnej semiwariancji w warunkach zmiennej koniunktury giełdowej - Rutkowska-Ziarko, Anna; Markowski, Lesław (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
This article aims at comparing Markovitz's portfolios with minimal semi-variance portfolios at various stages of the stock market. The assessment of the portfolios included the parameters of distribution of the rates of return, including selected risk measures and the phenomenon of distribution of return rates in time. The study was limited to the companies quoted on the Warsaw Stock Exchange between 2000 and 2005. The portfolios with a minimal semi-variance proved to be more profitable and less risky that Markovitz's portfolios. In most cases, both the SEM and Markowitz's portfolios were unstable with relation to the distribution of the return rates, but, notably, in the case of the SEM portfolios, the instability was greater. In both of the models compared, in all the three phases of study, the rise in the target rate of return entails an increase, not only in the risk (expressed by variance or semi--variance), but also in the possibility of a distribution change over time. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1176, s. 360-370